Design, validation, and testing of an observational tool for technical and tactical analysis in the taekwondo competition at the 2016 Olympic games - Menescardi, C.; Falcó, C.; Hernández-Mendo, A.; Morales-Sánchez, V. (Physiology & Behavior, 2020)
Observational methodology uses validated observational tools to collect information in sports with multiple variables that interact in the sporting context. Given the importance of data quality for observational tools, the purpose of this study was to design, validate, and test the reliability of a mixed observational instrument combining field formats and category systems for analyzing technical and tactical actions in an Olympic taekwondo (TKD) tournament. The instrument collects information of six criteria and 25 categories of the tactical and technical actions, kicking zone, laterality, kicking leg, guard, and score. A total of 2 374 actions were analyzed from 10 bouts involving 12 competitors in the 2016 Rio de Janeiro Olympic Games. The coefficients derived from the generalizability analysis (G coefficients) were used to check the accuracy, validity, and reliability of the tool created, while lag-sequential and polar-coordinate analysis were used to determine technical and tactical patterns of TKD athletes. The results showed optimal G coefficients and provide us with objective, valid, and reliable information on the bout situation analyzed, allowing us to extrapolate the data from our results to the sample population. The lag-sequential and polar-coordinate analyses showed that the competitors scored one point through direct attacks with linear techniques to the chest and performed circular actions with the back leg before and after scoring one point. Three points are scored by indirect attacks and subsequent counterattacks with spinning kicks to the trunk and head (using linear and circular techniques). These results reveal technical and tactical implications derived from the latest modifications of the regulations of this sport, as well as the need to adapt athletes` training for the next Olympic Games.